2020
DOI: 10.1007/s11325-020-02029-w
|View full text |Cite
|
Sign up to set email alerts
|

TLRs and RAGE are elevated in carotid plaques from patients with moderate-to-severe obstructive sleep apnea syndrome

Abstract: Background There is growing evidence that obstructive sleep apnea (OSA) promotes vascular endothelial dysfunction and atherogenesis. Pathways that mediate this pathology may include Toll-like receptors (TLRs) and receptor for advanced glycation end products (RAGE) which play a significant role in proinflammatory processes. The aim of this study was to measure the expression of the above-mentioned receptors in relation to OSA severity in carotid plaques obtained during open endarterectomy. Methods This prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…In pathogenesis of atherosclerosis, a pivotal role is played by innate immunity receptors such as toll-like receptors (TLR) and receptors for advanced glycation end products (RAGE) [67]. TLR and RAGE mediate in macrophages and leukocyte recruitment and are significantly involved in the initiation and progression of atherosclerosis [68]. This process is characterized by the accumulation of lipids, smooth muscle cell proliferation, cell apoptosis, necrosis, and fibrosis [69].…”
Section: Mmps In Pathogenesis Of Atherosclerosismentioning
confidence: 99%
“…In pathogenesis of atherosclerosis, a pivotal role is played by innate immunity receptors such as toll-like receptors (TLR) and receptors for advanced glycation end products (RAGE) [67]. TLR and RAGE mediate in macrophages and leukocyte recruitment and are significantly involved in the initiation and progression of atherosclerosis [68]. This process is characterized by the accumulation of lipids, smooth muscle cell proliferation, cell apoptosis, necrosis, and fibrosis [69].…”
Section: Mmps In Pathogenesis Of Atherosclerosismentioning
confidence: 99%
“…Two recent studies conducted on plaques of patients with OSA support this notion. In a prospective study, Olejarz et al reported that the expression of toll-like receptors (TLRs) and the receptor for advanced glycation end products (RAGE) were significantly increased in carotid plaques of moderate to severe OSA when compared with controls or with mild OSA ( 41 ). These receptors play a pivotal role in carotid plaque instability and rupture ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…That confirms cysteinyl-leukotrienes (CysLT) pathway activation as a potential mechanism responsible for developing atherosclerosis connected with IH [ 22 ]. Another study trying to explain OSA-dependent atherogenesis found an increased expression of toll-like receptors (TLRs) and receptor for advanced glycation end-products (RAGE) in atherosclerotic plaques from patients with severe OSA [ 23 ].…”
Section: Molecular Consequences Of Hypoxia/reoxygenation (H/r) On Endothelial Function In Osa Before Cpap Treatmentmentioning
confidence: 99%
“…(TLRs) and receptor for advanced glycation end-products (RAGE) in atherosclerotic plaques from patients with severe OSA [23].…”
Section: Molecular Consequences Of Hypoxia/reoxygenation (H/r) On Endothelial Function In Osa Before Cpap Treatmentmentioning
confidence: 99%